P171 Pneumocystis Jirovecii Pneumonia in non-HIV immunosuppressed patients: Acase series. (20th September 2022) - Chakraborty, Sourabh; Soman, Rajeev; Joe, Geethu
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objective: Increased usage of immunosuppressive medications and lack of guidance about when to initiate primary Pneumocystis Jirovecii Pneumonia (PCP) prophylaxis has led to a rising incidence of PCP in non-HIV immunosuppressed patients. The objective of this case series is to review clinical challenges in diagnosis and management of these patients. Patients, methods, and results: This is a retrospective case series of all 6 cases which were seen at Jupiter Hospital from January 2020 to October 2021 (Table 1). Conclusion: The presence of the above-mentioned predisposing factors should raise the suspicion of PCP. Non-invasive investigations like serum LDH, BDG, PET CT scan/HRCT scan of chest can help in the diagnosis. This can be confirmed by BAL PCR, which is both, more sensitive and specific than immunofluorescence microscopy. Trimethoprim- sulfamethoxazole (TMP- SMX), the standard treatment, cannot be used in some circumstances and alternate treatment may have to be used. Guidance about prophylaxis, antimicrobial therapy for PCP, and adjuvant steroid therapy in non-HIV patients is unavailable, which is an unmet clinical need.